The RCMP, the Special Branch, and the Early Days of the Communist Party of Canada: A Documentary Article - Kealey, Gregory S. (Labour / Le Travail, 1992)
Introduces five sets of documents that shed light on the early years of the Communist Party of Canada and the RCMP security apparatus that surveilled and infiltrated it. The materials include in-camera CPC bulletins and reports, transcripts of secret speeches by Pan-American Bureau agent Charles Scott to party members in Regina and Edmonton, RCMP correspondence with the UK's Special Branch, and RCMP security bulletins. The materials were released by the Public Record Office in London, England, and through a freedom-of-information request with the Canadian Security Intelligence Service. Concludes that the documents are indicative of the close relationship between Canadian and British security agencies and their joint preoccupation with the threat of international communism.
Keywords: Canada; Communist Party of Canada; England; GREAT Britain. Public Record Office; LABOUR/LE Travail (Book); ROYAL Canadian Mounted Police; Radicalism; Socialism